2018
DOI: 10.1136/bmjopen-2018-022768
|View full text |Cite
|
Sign up to set email alerts
|

Changing use of antidiabetic drugs in the UK: trends in prescribing 2000–2017

Abstract: ObjectivesGuidelines for the use of drugs for type 2 diabetes mellitus (T2DM) have changed since 2000, and new classes of drug have been introduced. Our aim was to describe how drug choice at initiation and first stage of intensification have changed over this period, and to what extent prescribing was in accord with clinical guidelines, including adherence to recommendations regarding kidney function.DesignRepeated cross-sectional study.SettingUK electronic primary care health records from the Clinical Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
132
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(145 citation statements)
references
References 22 publications
12
132
1
Order By: Relevance
“…Similar trends in antidiabetic use have also been observed in other countries, but with smaller changes and variation in use for specific antidiabetic drugs . In 2017, the use of sulphonylureas and GLP‐1RAs each accounted for 8% of the total antidiabetic drug use in Denmark.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar trends in antidiabetic use have also been observed in other countries, but with smaller changes and variation in use for specific antidiabetic drugs . In 2017, the use of sulphonylureas and GLP‐1RAs each accounted for 8% of the total antidiabetic drug use in Denmark.…”
Section: Discussionsupporting
confidence: 61%
“…Physicians may add on any available antidiabetic drug while taking the heterogeneous cardiovascular and glycaemic risk profile, kidney function, age and socio‐economic status of their patients into account. To date, a few studies have reported on time trends in the utilization of antidiabetic drugs, but little is known about the correlation between, for example, antidiabetic drug use and costs . Knowledge in this area may provide important insights into and awareness of healthcare costs and help guide diabetologists, specialists in internal medicine, general practitioners and other healthcare professionals in choosing the appropriate antidiabetic drug for their patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Choice between these agents is left largely to the clinician and patient. Recent studies show that there have been marked changes in which agents are initiated after metformin, with declining use of sulphonylureas and increasing and earlier use of DPP‐4 inhibitors and SGLT2 inhibitors in both the United States, Europe and the United Kingdom …”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycaemia risk is greater with sulphonylureas and insulin relative to other agents . Despite these known differences in non‐glycaemic effects between agents, evidence of the impact of recent changes in prescribing on population‐level patient outcomes is limited . In the present study we aimed to describe changes in prescribing of glucose‐lowering drugs for patients initiating first‐ to fourth‐line therapy between 2010 and 2017 in the United Kingdom, a setting where prescribing does not reflect the ability of patients to pay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation